Santiago Ramón y Cajal and Ivan Petrovic Pavlov: their parallel scientific lives, schools and nobel prizes - Rozo, Jairo A.; Rodríguez-Moreno, Antonio (Frontiers in Neuroanatomy, 2015)
Santiago Ramón y Cajal was not only a great scientist but he was also a dedicated teacher who managed to create his own School in Spain. Cajal was active at the end of the XIX and the beginning of the XX century, a period in which Ivan Petrovich Pavlov, another great contemporary scientist, also established a strong School in Russia. While these two acclaimed scientists shared a similar vision on science, a view they also conveyed to their disciples, they applied quite distinct criteria in the way they dealt with their followers. Interestingly, despite the geographic and idiomatic barriers that had to be overcome, the paths of these two great figures of XX century science crossed at least three times. First when they competed for the City of Moscow Prize, second when they both attended the “Congreso Internacional de Medicina de Madrid” (Medicine International Congress in Madrid) in 1903 and finally, they competed on four consecutive occasions for the Nobel Prize in Physiology or Medicine. Here we discuss their scientific vision, their different attitudes in the interaction with disciples and the distinct circumstances in which their paths crossed.